The influence of art on Singaporean tertiary undergraduates’ attitudes towards migrant workers - Aw, Qinxin (2011)
In this paper, we aim to determine if art can favourably influence the attitudes of Singaporean undergraduates towards migrant workers in Singapore, in particular, national identity, multicultural ideology, perceived consequences of immigration, and integrated acculturation. An art exhibition consisting of artworks produced by students who were enrolled in a drawing course in the Nanyang Technological University was held for a duration of two weeks, and online platforms such as Facebook were used for the promotion of the exhibition. Pre and post-test survey data was collected from 113 Singaporean undergraduates aged 19 to 25 and two focus groups discussions were conducted in groups of five. Through exposure to art, national identity and perceived consequences of immigration in the experimental group were hypothesized to decrease, and multicultural ideology and integrated acculturation were expected to increase. To measure the changes in attitude, a linear framework for attitude change was proposed and variables were placed accordingly to the framework. Participants in the experimental group (n=83) experienced a significant decrease in national identity after viewing art while participants in the control group (n=30) did not experience a change in national identity. Results were discussed according to the elaboration likelihood model and selective exposure theory, specifically that art can only bring about the first stage of attitude change, while deeply entrenched values are difficult to change with just an art campaign.